Manufacturing process laboratory manual - Mohd. Zaidi Sidek; Mohd Syahidan Kamarudin (Penerbit Universiti Malaysia Pahang, 2014)
This manual is designed to provide hands-on experiences to engineering students by adopting the outcome based learning (OBE) method during laboratory session